PENGARUH INTERNET FINANCIAL REPORTING DAN TINGKAT PENGUNGKAPAN INFORMASI MELALUI WEBSITE TERHADAP FREKUENSI PERDAGANGAN SAHAM PERUSAHAAN YANG TERDAFTAR DI INDEKS KOMPAS 100 PERIODE 2013-2017 - Hanifa Sri Nuryani; Reza Muhammad Rizqi; Nurul Apriani (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2019)
This study aims to examine the effect of Internet Financial Reporting and the Level of Disclosure of Information Through Websites Against the Frequency of Stock Trading of Companies Listed in the Kompas 100 Index of 2013- 2107. This research is quantitative research. The data collection method used in this study is the study of documentation on Indonesian Stock Exchange (Idx) facts in 2013-2017 to obtain stock trading frequency recapitulation during 2013-2017, literature study to collect data as a theoretical basis and observing websites to see website addresses company. The sampling technique uses purposive sampling. Data analysis used is multiple linear regression analysis. Based on the results of the study it can be concluded that Internet Financial Reporting affects the frequency of trading in company shares, and the level of disclosure of information through the website does not affect the frequency of trading in company shares. So, it can be said that companies that implement IFR have a higher frequency of trade than companies that do not implement IFR. While the level of website information disclosure is not enough to provide complete information to investors as the party who will assess the company's performance and prospects in the future and make decisions regarding investment.